Original articleCarotid atheromatous plaques’ instability. Practical implication of morphologic assessment - Masztalewicz, Marta; Nowacki, Przemysław; Bajer-Czajkowska, Anna; Kotfis, Katarzyna; Biernawska, Jowita; Żukowski, Maciej; Gutowski, Piotr (Folia Neuropathologica, 2012)
The only method giving the possibility of a thorough assessment of plaques instability, is a histologic examination. Three plaques categories were distinguished: unstable, potentially unstable and stable. The distribution of particular types of plaques was similar in symptomatic and asymptomatic patients. Over three quarters of lesions which could correspond to stable plaques in a macroscopic assessment, microscopically fulfilled the criteria for unstable or potentially unstable ones (the number of confirmed stable lesions vs the number of unconfirmed ones, 13 vs. 51 respectively, p < 0.0001). In a microscopic assessment made for all the plaques altogether, 52 plaques (58.4%) were considered unstable; 18 (20.2%) fulfilled the criteria for potentially unstable ones. The remaining 19 plaques (21.4%) were classified as plaques of stable structure. Unstable plaques constituted a significant majority (unstable vs potentially unstable and unstable vs. stable, p = 0.0006 and p = 0.0008 respectively). Due to the fact that majority of carotid atheromatous plaques appear to be unstable or potentially unstable because of the inflammation and related mechanisms, the role of the inflammatory-immunologic component of atherosclerosis should be used in prophylaxis of stroke and the new therapeutic concepts worked out.